Concept of Nonverbal Communication by Using Sign Language by Al-Jahidz l Mafhum al-Ittisal Goiru al-Lafdzi bi Istikhdam Lugah al-Isyarah 'inda Al-Jahidz - Muflihah, Muflihah (Universitas Islam Negeri Raden Intan Lampung, 2021)
Most of the generation (Arabic linguistic academics) have not comprehended the linguistic theories which initiated by Al-Jahid. This study aims to research on the concept of communication with the signs in Al-Jahid works. To identify these problems in depth and thoroughly, qualitative descriptive study was used. The primary data sources of this research were various sources, mainly Al Jahid book with documentation from the works of Al-Jahid and observation techniques based on the other books about Jahid ‘s point of view, such as Kamal Bisyri and other linguists. The results of this study concluded that: Al-Jahiz is an Arabic language expert who discussed the theory of non-verbal communication. In the case of learning a language, we also have to comprehend the theory of communication, especially communication with signs by Al-Jahiz. His thoughts were followed by several contemporary scholars. Thus, it is highly recommended to the Arabic researchesr to figure out the works of previous Arabic scholars which had been discussing about contemporary linguistic.